LEVELS OF ONLINE LEARNING EFFECTIVENESS IN THE TIME OF THE COVID-19 PANDEMIC USING DIFFERENT APPLICATIONS LEARNING BY STUDENT'S PERCEPTION - Kristianto, Nova; Delvia, Dessy (Epsilon: Jurnal Pendidikan Matematika, 2021)
Abstract: This study aims to determine the level of effectiveness of online learning during the Covid-19 pandemic by using a variety of learning applications. This research is a case study and is also a descriptive or qualitative research. The number of samples taken was 100 respondents (students). Then the data were analyzed using Likert scale analysis, and the results of the Likert scale analysis stated that most students (18 students or 18%) online learning during the Covid-19 pandemic using a variety of learning applications was very effective and (47 respondents or 47%) stated online learning during the Covid-19 pandemic using a variety of effective learning applications. So it can also be said that online learning using a variety of applications that are expected to prevent transmission and break the chain of spread of Covid-19 is at an effective level. Even though online learning using various applications in the Covid-19 pandemic conditions has been effective, 49 students or (49%) hope that learning can be carried out with (Blended), namely a combination of online and face-to-face learning.